PENERAPAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES PADA MATERI TOKOH-TOKOH SEJARAH UNTUK MENINGKATAN HASIL BELAJAR SISWA KELAS V SDN GUNUNGSARI - Suyanti, Putri; Hanifah, Nurdinah; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2017)
Preliminary data shows 6 of 20 grade school students gunungsari as the subject of study has not reached kkm. It is because several factors of teachers and students. Their effort to improve these problems by applying model examples non examples. Researchers used the methodology quantitative and qualitative spiral model research class action (PTK) start the planning stages , implementation , observation and reflection. Increasing proven from the observation the planning stage cycle I (86,7%), cycle II (100%), and the cycle III (100%). The performance of teachers cycle I (80%), cycles II (95%), and cycle III (100%). The activity of students cycle I (75,4%), cycle II (82,1%), and cycle III (90%). Study results students cycle I ( 55 % ), cycle II (75%), and cycle III (90%). Thus through model Examples Non Examples , the learning and linguistic survey intelligence SDN Gunungsari Kecamatan Sumedang Utara Kabupaten sumedang increased.